2009
DOI: 10.1002/iroh.200711036
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton and Epipelon Responses to Clear and Turbid Phases in a Seepage Lake (Buenos Aires, Argentina)

Abstract: Annual changes in the algal density and concentrations of chlorophyll a, total phosphorus, and organic matter were analyzed in water and sediments at four sites characterized by the presence or absence of submerged and emergent macrophytes, during turbid-and clear-water conditions to determine the contribution of the algal components of the plankton and the epipelon and to identify the most typical species in each community. Three states were recognized: one turbid and two clear, with different submerged macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 43 publications
2
29
1
Order By: Relevance
“…Thus, the periphyton presented a dual-period variation pattern (i.e. turbid to clear) in contrast to the 3-period dynamic observed by Casco et al (2009) for the phytoplankton.…”
Section: Epiphyton Variations In Space and Timementioning
confidence: 64%
See 2 more Smart Citations
“…Thus, the periphyton presented a dual-period variation pattern (i.e. turbid to clear) in contrast to the 3-period dynamic observed by Casco et al (2009) for the phytoplankton.…”
Section: Epiphyton Variations In Space and Timementioning
confidence: 64%
“…With respect to time, our analysis of the environmental variables at both of the sampling sites resulted in a discrimination of 3 periods that coincided with the equilibrium states previously identified by Casco et al (2009) on the basis of data gathered at 4 sampling points plus a consideration of the biological variables that were necessary for the establishment of equilibrium.…”
Section: Epiphyton Variations In Space and Timementioning
confidence: 86%
See 1 more Smart Citation
“…Nevertheless, as our two experiments were conducted in different seasons, further studies are needed to analyze possible seasonal changes in periphyton composition. In a recent study, Casco et al (2009) characterized the epipelon community in the Pampean shallow Lake Lacombe and found that the algal groups change when the lake shifts from a clear to a turbid state.…”
Section: Discussionmentioning
confidence: 99%
“…However, the information about the periphyton community of this region is still scarce (e.g., Cano et al, 2008;Casco et al, 2009). In a recent study, we compared the periphyton community with phytoplankton under contrasting optical scenarios, and found that in a clear-vegetated lake the algal fraction of periphyton was dominant (Sánchez et al, 2010).…”
Section: Introductionmentioning
confidence: 97%